MOBILE APP FOR SOCIAL ENGAGEMENT TO ASSIST PEOPLE WITH DISABILITIES AT TOURIST SITES - Rosa, Marcos Roque da; Pereira, Eliane Nascimento (Interfaces Científicas - Humanas e Sociais, 2021)
Accessibility can aid people with disabilities to participate enthusiastically in society with equitable access and fair opportunities. Accessible tourism enables them to become more included and enjoy their experiences. Technology has facilitated travel for individuals with disabilities, and a Geographic In-formation System (GIS) can provide tourist guidance, navigable digital maps, and enable the searching of places information. To support people with disabilities planning and moving more independently, the objective of this article is to propose an application to assist them by providing accessibility information about tourist places. To realize this work, research about GIS related to disabled persons was carried out, a pilot project to validate the idea and the app development proposed. As a result, the map of the accessible places was developed using free GIS technologies. This app will encourage people with disa-bilities to move more safely and comfortably, and increase open data in GIS by civil engagement